User-Defined Classification for Email System using Back Propagation Algorithm - Arzare, Arichi; Chaudhari, Suneha; Desai, Sayalee; Jadhav, Sonali (International Journal of Computer Sciences and Engineering, 2015)
These days email system is one of the major sources of communication and users’ depend heavily on it. Even after the evolution of new mobile applications, social networks etc. emails are extensively used on both personal and professional platforms. Pertaining to this extensive use, inboxes these days usually become a chunk with unnecessary messages from social media, advertisements, subscriptions etc. which might not be of that much importance. Thus there’s a need of classification so that the user does not have to surf through the chunk for one particularly important mail. In this paper, we propose a solution for email classification using back propagation technique which has user defined categories where word search is made on the content of the email. The output of this solution will give the user a selected number of emails according to the category he/she chooses.